Pemberdayaan Kelompok Tani dalam Meningkatkan Kualitas Produksi Tebu dengan Memperhatilan Masa Panen - Zelmi Sriyolja; Aulia Rizki Alda; Firyessi Firyessi; Isna Juwita (PELANTAR PRESS, 2025)
Sugarcane (Saccharum officinarum L.) is a strategic plantation commodity in Indonesia, functioning as the primary raw material for sugar and traditional sweeteners such as gula saka. In Nagari Bukik Batabuah, West Sumatra, gula saka production holds economic, social, and cultural significance; however, product quality remains inconsistent, particularly due to inappropriate harvest timing and post-harvest handling. This study aims to examine the influence of sugarcane harvest period on the quality of gula saka produced by local farmers and traditional processors (pangilang saka). A descriptive qualitative approach was applied through field observations, in-depth interviews, and documentation, with informants selected using purposive sampling. The results indicate that harvest age and delays between harvesting and processing significantly affect the chemical composition of sugarcane juice, especially sucrose levels, reducing sugars, and phenolic compounds. Harvesting at an immature stage leads to low sugar yield and weak sweetness, while over-mature harvesting or delayed processing accelerates sucrose degradation, resulting in darker color and inferior flavor quality. These findings demonstrate that variations in gula saka quality are strongly associated with harvest management rather than processing methods alone. The study concludes that strengthening farmers’ capacity in determining optimal harvest timing and improving post-harvest practices is essential to enhance product quality, preserve local wisdom, and improve the sustainability of traditional sugarcane-based industries